(untitled) (Philological Studies, 2019)
The research topic of this paper are anthropomorphism and zoomorphism in Croatian, Russian and German zoonymic idioms which have, at least, one wild animal component. The two terms come from the field of cultural zoology. Anthropomorphism is, at its most general, the assignment of human characteristics to animals, and zoomorphism is a human having animal like characteristics. Anthropomorphic representation dates to Paleolithic art, when some drawings of animals included characteristically human features. Ethologists have proved that in the animal world there are some elements of culture, which means that animals are doubly related to culture: they have their own culture and they are important for shaping the human culture. The main aim of this paper is to show which Croatian, Russian and German idioms with wild animal as a component were created based on anthropomorphism, and which of them were based on zoomorphism, and to what extent those idioms have had influence on prejudice about wild animals embedded in the subconscious minds of Croats, Russians and Germans.